9. Dilema Hak Asasi Manusia Di Asia Tenggara: Ketiadaan Peran Asean dalam Kasus Perekrutan Tentara Anak di Myanmar dalam Perspektif English School - H, Alvian Rizky; Putranti, Ika Riswanti; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
ASEAN as a regional organization of Southeast Asia is considered absent and did notcontribute in the case of child soldiers’ recruitment in Myanmar. ASEAN, which hashuman rights commission such as the ASEAN Intergovernmental Commission on HumanRights (AICHR) and the ASEAN Commission on the Promotion and Protection of theRights of Women and Children (ACWC), has failed in promoting the protection of humanrights and child rights in the case of child soldiers in Myanmar. The absence of ASEAN iscontradictory to the actions taken by UN, Human Rights Watch (HRW), Child SoldierInternational (CSI) and neighboring countries in preventing and stopping the recruitmentof child soldiers in Myanmar. This research is aimed to analyze the reason behind suchsituation. Based on the view of pluralist international society, the absence of ASEAN inchild soldiers’ case in Myanmar is caused by two main reasons. First, non-interferenceprinciple which is upheld by ASEAN to respect the sovereignty of Myanmar. Second,inability to reach consensus within ASEAN, while consensus itself is decision makingprinciple in ASEAN aimed to avoid any action which may compromise the sovereignty ofother member states. On the other hand, the opposite responses given by UN, NGOs andneighboring country of Myanmar can be viewed by solidarist international society, whichargued that such actions are forms of protection of the values of individual freedom andhuman rights.